2005
DOI: 10.1007/s00534-004-0933-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-branch resection of the pancreas

Abstract: The treatment of intraductal papillary mucinous tumors (IPMT) of the pancreas is still controversial. In this report we describe a single-branch resection of the pancreas (SBRP), which is a new method for the removal of branch-type IPMT of the head of the pancreas. A multilobular cystic lesion (50 x 40 mm) in the head of the pancreas was incidentally detected in an asymptomatic 40-year-old man who underwent a routine ultrasound examination. The tumor was carefully removed along the border of the cyst and the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Lastly, minutely injured duct was repaired without stent insertion, without leakage after operation. Sata et al [9] experienced pancreatic leakages which were managed by the insertion of an endoscopic nasopancreatic drainage tube. In segmental pancreas resection, pancreatic leakage rates reach up to 40% [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lastly, minutely injured duct was repaired without stent insertion, without leakage after operation. Sata et al [9] experienced pancreatic leakages which were managed by the insertion of an endoscopic nasopancreatic drainage tube. In segmental pancreas resection, pancreatic leakage rates reach up to 40% [20][21][22] .…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, pancreatic duct preserving procedures were reported, such as inferior pancreatic head resection, and uncinate process resection [5,7,8] . More minimal pancreatic head resections were performed such as single branch resection of the pancreas, and ductal branch-oriented minimal pancreatectomy [9,10] . Pancreatic leakage is one of the most frustrating complications after limited pancreatic resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have suggested that patients with non‐invasive IPMN have a favorable prognosis after surgical resection . Thus, a variety of types of partial pancreatic resections have been advocated for treating these low‐grade malignant tumors . Takada [20] presented the procedure of ventral pancreatectomy.…”
Section: Discussionmentioning
confidence: 99%